1999
DOI: 10.1093/ps/78.7.1065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of evaporative air chilling and storage temperature on quality and shelf life of fresh chicken carcasses

Abstract: The effect of evaporative air chilling on quality of fresh chicken carcasses was compared with air chilling as reference method. Cooling efficiency and total heat loss were significantly higher for evaporative air chilling. The chilling method was of great importance for weight loss. Chicken chilled in cold air lost considerably more weight than chicken cooled by evaporative air chilling; the difference was 1.8%. The chilling method also affected the skin color and the amount of moisture on skin surface. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 2 publications
4
21
0
2
Order By: Relevance
“…It is generally recognized that both chilling methods and scalding types can influence carcass skin color (yellowness or whiteness), swelling, shrinkage, and the finished carcass weight (Veerkamp, 1981(Veerkamp, , 1986(Veerkamp, , 1991. Mielnik et al (1999) found that chicken chilled by EAC had a lighter and less intense yellow color than those chilled by AC because the sprayed water prevented the surface from dehydrating and maintained a lighter skin color. Northcutt (1997) reported that both carcass color and visual appearance are important because consumers receive their first impressions visually, and based on this impression, they often decide whether to buy the product.…”
Section: Introductionmentioning
confidence: 97%
“…It is generally recognized that both chilling methods and scalding types can influence carcass skin color (yellowness or whiteness), swelling, shrinkage, and the finished carcass weight (Veerkamp, 1981(Veerkamp, , 1986(Veerkamp, , 1991. Mielnik et al (1999) found that chicken chilled by EAC had a lighter and less intense yellow color than those chilled by AC because the sprayed water prevented the surface from dehydrating and maintained a lighter skin color. Northcutt (1997) reported that both carcass color and visual appearance are important because consumers receive their first impressions visually, and based on this impression, they often decide whether to buy the product.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, quick chilling can significantly reduce weight loss. Choice of the chilling method is therefore important for the quality of the finished product (Mielnik et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…O método de resfriamento evaporativo de carcaças de frango, um processo misto utilizando água e ar frio forçado, foi desenvolvido com a intenção de combinar as vantagens das técnicas de imersão em água e por ar forçado. Neste método, durante um processo de resfriamento de carcaças de frango por ar forçado em câmaras frias, utilizando baixas temperaturas (de 1 °C a 4 °C), as carcaças podem ser rapidamente imersas água fria ou pulverizadas por uma fina camada de água (Mielnik et al, 1999). O resfriamento evaporativo aumenta a taxa de transferência de calor, minimiza a perda de massa e reduz o ressecamento da pele das carcaças de frango na comparação com o processo realizado somente por ar forçado (Barbut, 2002;Jeong et al, 2011a).…”
Section: Introductionunclassified
“…O resfriamento evaporativo aumenta a taxa de transferência de calor, minimiza a perda de massa e reduz o ressecamento da pele das carcaças de frango na comparação com o processo realizado somente por ar forçado (Barbut, 2002;Jeong et al, 2011a). Estudos anteriores avaliaram os efeitos das técnicas de resfriamento em imersão em água e ar forçado; ar forçado e o resfriamento evaporativo com respeito à qualidade, rendimento de resfriamento e extensão da vida útil da carne de frango processada (Mielnik et al, 1999;Young e Smith, 2004;Savell et al, 2005;Huezo et al, 2007;Carroll e Alvarado, 2008;Jeong et al, 2011a;Jeong et al, 2011b). Neste contexto, o objetivo deste estudo foi investigar o tempo de resfriamento e a perda de massa de carcaças de frango submetidas ao resfriamento combinado de ar forçado e imersão em água em diferentes velocidades e umidades relativas do ar em um mesmo aparato experimental.…”
Section: Introductionunclassified